Impact of secukinumab on patient-reported outcomes in moderate to severe plaque psoriasis: a review of clinical studies. (1st February 2021) - Galluzzo, Marco; Talamonti, Marina; Manfreda, Valeria; Silvaggio, Dionisio; Tartaglia, Chiara; Roberto, Denis; Campione, Elena; Bianchi, Luca
ABSTRACT: Introduction : Perception of illness varies among individuals and psoriasis of the same severity can be perceived in different ways by patients, making it essential to evaluate quality of life (QoL) since it can provide information on the impact of the disease on the patient's overall well-being. The use of patient-reported outcomes in clinical trials provides the ability to integrate objective clinical assessment with the patient's perception of their own state of health. Areas covered : The introduction of anti-IL17 agents in clinical practice has given patients the possibility to achieve a PASI90 response (almost clear skin) or even higher (complete clear skin) in the majority of patients. There is accumulating evidence in support of PASI90 response as the new standard goal for therapy based on its greater correlation with health-related QoL. The present review summarizes current knowledge of the effects of secukinumab on the QoL of patients with psoriasis using patient-reported outcome measures. Expert Opinion : Secukinumab, the first approved drug of this new class, has fully reached a new therapeutic paradigm not only in terms of clinical efficacy, but also in terms of patient satisfaction and self-rated health.